2018
DOI: 10.1002/pits.22139
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement and mathematics achievement: Unraveling main and interactive effects

Abstract: The present study explored the relationships between student engagement and mathematics achievement for 295,416 15-yearold students from 11,767 secondary schools in 34 countries who participated in the Program for International Student Assessment (PISA) 2012. Affective engagement was measured by students' mathematics interest (InterestMath) and perceived usefulness of schooling (PerceptionSch), behavioral engagement by behaviors facilitating mathematics learning (BehaviorMath) and participation in mathematics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 57 publications
3
36
0
1
Order By: Relevance
“…The conceptualization of learning outcomes in this model comprises both short-and longterm achievement outcomes (e.g., standardized achievement, class achievement). Consistently, prior variable-centred work has shown that higher engagement is predictive of better math achievement (Fung, Tan, & Chen, 2018;Wang et al, 2016). For engaged students, the investment of cognitive and affective resources in math activities may serve as critical self-regulative and affective resources that maximize task performance.…”
Section: Outcomes Of Math Engagement Profile Membershipmentioning
confidence: 53%
“…The conceptualization of learning outcomes in this model comprises both short-and longterm achievement outcomes (e.g., standardized achievement, class achievement). Consistently, prior variable-centred work has shown that higher engagement is predictive of better math achievement (Fung, Tan, & Chen, 2018;Wang et al, 2016). For engaged students, the investment of cognitive and affective resources in math activities may serve as critical self-regulative and affective resources that maximize task performance.…”
Section: Outcomes Of Math Engagement Profile Membershipmentioning
confidence: 53%
“…Tutors benefit as they reinforce their knowledge by answering the tutees' questions. These interactions between tutors and tutees promote active learning and foster student inclusion, as all students participate in the process [39,40].…”
Section: Peer Tutoringmentioning
confidence: 99%
“…Whereas, feedback has significant increase in cognitive engagement of both average achievers and low achievers cognitive engagement (e.g. Fung, Tan & Chen, 2018;Fielding-Wells & Makar, 2008;Kong & Hoare, 2011). There is less literature on relationship of components of engagement on different ability groups separately.…”
Section: Discussionmentioning
confidence: 99%